Application of the Principle of Freedom of Contract in Nominee Agreements Regarding the Prohibition of Land Ownership by Foreign Citizens - Ni Ketut Sucia Dewi Lestari; Anak Agung Ayu Intan Puspadewi (Jurnal ISO: Jurnal Ilmu Sosial, Politik dan Humaniora, 2026)
A nominee agreement is a practice commonly used by foreign nationals to acquire land in Indonesia by using the name of an Indonesian citizen as the formal right holder. This study aims to analyze the legal construction of nominee agreements as a form of legal evasion (rechtsontduiking) and their juridical implications for land ownership status. The research employs a normative legal method with statutory and conceptual approaches. The findings indicate that nominee agreements constitute a form of legal circumvention that undermines the prohibition on foreign land ownership under the Basic Agrarian Law (UUPA) through seemingly lawful arrangements that, in essence, violate Articles 21 and 26 of the UUPA. Such agreements fail to meet the objective requirement of a lawful cause as stipulated in the Indonesian Civil Code (KUH Perdata), rendering them null and void from the outset. The juridical implication is that the foreign national loses all rights to the land and cannot claim restitution of invested funds, while both the foreign national and the Indonesian nominee are deemed to have committed an unlawful act under Article 1365 of the Civil Code. Courts are therefore obliged to declare nominee agreements null and void by law, in accordance with Supreme Court Circular Letter (SEMA) No. 10 of 2020.